2017
DOI: 10.1121/1.4978342
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and perceptual speech characteristics of native Mandarin speakers with Parkinson's disease

Abstract: This study examines acoustic features of speech production in speakers of Mandarin with Parkinson's disease (PD) and relates them to intelligibility outcomes. Data from 11 participants with PD and 7 controls are compared on several acoustic measures. In speakers with PD, the strength of association between these measures and intelligibility is investigated. Speakers with PD exhibited significant differences in fundamental frequency, pitch variation, vowel space, and rate relative to controls. However, in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
2
18
3
4
Order By: Relevance
“…English speaking PD patients with hypokinetic dysarthria have the same salient speech features as PD patients who speak other languages, such as Spanish and Korean [12]. Japanesespeaking PD patients also present with dysarthria and have the same speech characteristics as English-speaking patients [13].…”
Section: Introductionmentioning
confidence: 97%
“…English speaking PD patients with hypokinetic dysarthria have the same salient speech features as PD patients who speak other languages, such as Spanish and Korean [12]. Japanesespeaking PD patients also present with dysarthria and have the same speech characteristics as English-speaking patients [13].…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, dysarthria may manifest differently across languages at segmental and prosodic levels (Hsu et al . 2017, Liss et al . 2013), as might the effects of global cueing strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of vowel acoustics in dysarthria have primarily been conducted in English speakers, as reviewed above, with some evidence in other languages, including Mandarin (Liu et al 2005, Hsu et al 2017, Mou et al 2019 and French (Martel-Sauvageau et al 2015). Similar to findings in English, these studies have demonstrated a reduction of the acoustic vowel space among speakers with dysarthria in comparison with healthy peers (Mandarin) or acoustic changes following treatment (French).…”
Section: Speech Intelligibility and Acoustic Measuresmentioning
confidence: 90%
“…As its name implies, the VSA calculates the acoustic area within the corner vowels, as either vowel quadrilateral (four corner vowels /ɑ/, /ae/, /i/, /u/) or vowel triangle (tVSA; three corner vowels /ɑ/, /i/, /u/) in the correlating vowel systems. A reduction of this area has been demonstrated in dysarthric speech in both developmental (e.g., Higgins andHodge 2002, Mou et al 2019), and acquired (Hsu et al 2017) dysarthria, and is attributed to reduced movement of the articulators to their typical placement during vowel production (also termed articulatory undershoot; Kent and Kim 2003). The VSA metric was found to correlate with degree of centralization and dysarthria severity in individuals with dysarthria of mixed aetiologies (Fletcher et al 2017).…”
Section: Vowel Space Area (Vsa)mentioning
confidence: 96%